2011
DOI: 10.1016/j.ultsonch.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic transesterification of Jatropha curcas oil assisted by ultrasonication

Abstract: Ultrasonication used for the production of fatty acid methyl ester from non-edible vegetable oil using immobilized lipase (Chromobacterium viscosum) as a catalyst from Enterobacter aerogenes to make the process fully ecologically and environmental friendly. The optimal conditions for biodiesel production is the molar ratio oil to methanol 1:4, catalyst concentration 5 wt.% of oil, reaction time 30 min, ultrasonic amplitude 50% (100 W/m(3)) and cycle 0.7s. ultrasonication reduce the reaction time comparing to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 19 publications
4
38
0
4
Order By: Relevance
“…Many interesting works using ultrasound to enhance biodiesel conversion with reaction catalyzed by enzymes are described in the literature (Waghmare et al, 2015;Lerin et al, 2014;Awadallak et al, 2013;Batistella et al, 2012;Fiametti et al, 2012;Kumar et al, 2011). However, we have not found reports that describe the ethanolysis of Jatropha curcas oil under ultrasound irradiation.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Many interesting works using ultrasound to enhance biodiesel conversion with reaction catalyzed by enzymes are described in the literature (Waghmare et al, 2015;Lerin et al, 2014;Awadallak et al, 2013;Batistella et al, 2012;Fiametti et al, 2012;Kumar et al, 2011). However, we have not found reports that describe the ethanolysis of Jatropha curcas oil under ultrasound irradiation.…”
Section: Introductionmentioning
confidence: 83%
“…Soumanou et al (2012) tested different immobilized enzymes for alcoholysis of Jatropha curcas oil and achieved the highest conversion (93%) using immobilized Pseudomonas cepacia lipases on Accurel 1282 after 16 h, whereas the lowest conversion was found with Novozym 435. A study of Jatropha curcas oil methanolysis in ultrasound showed 84.5% conversion of methyl esters using immobilized Enterobacter aerogenes lipase on silica, molar ratio oil to methanol 1:4, reaction time 30 min, ultrasonic amplitude 50% (100 W/m 3 ) and cycle 0.7 s (Kumar et al, 2011).…”
Section: Kinetic Study: Effect Of Enzyme Concentrationmentioning
confidence: 99%
“…On the other hand, enzymatic transesterification requires a longer reaction time and a great amount of catalyst; the enzymes are expensive and can be inhibited by the glycerol during the process [32]. It has been demonstrated that the use of ultrasound improves the effectiveness of enzymatic transesterification, resulting in a shorter reaction time, but with a very high energy cost [33].…”
Section: Influence Of the Reaction Timementioning
confidence: 99%
“…Several authors have reported processes in batch reactors [29][30][31][32] and have described a significant promoting effect that enables lower catalyst and alcohol loading to be used in transesterification [33][34][35]. Under sonochemical conditions a reaction normally takes place at low or ambient temperature [3,36,37].…”
Section: Biodiesel Production Using Usmentioning
confidence: 99%